Becoming a nurse: "it's just who I am". Issue 2 (5th December 2005) - Flaming, D
Abstract : In any research study, researchers situate themselves, either explicitly or implicitly, within a variety of frameworks when studying phenomena. From a research perspective, the study will be more robust if these frameworks and the accompanying assumptions are compatible with each other; otherwise, the project may lack coherence. Ricoeur offers a methodological perspective—that is, an interpretive theory as reflected in mimesis, which is congruent with his ontological theory of self identity ( ipse - and idem -identity). To illustrate Ricoeur's frameworks when researching the self identities, I use examples from a research study in which I asked senior nursing students to explore their experience of becoming a nurse. I do not intend for this article to be a comprehensive research report, but I present it as an exemplar of how Ricoeur's ideas can guide other researchers studying self identity. I labelled my study a narrative research project and assumed that becoming a nurse means developing a self identity as a nurse. While self identity is often framed in psychological terms, Ricoeur uses a philosophical perspective when exploring this concept. I conclude the paper by suggesting (a) that Ricoeur can guide any project in which researchers ask participants to describe "becoming" a person with illness, sickness or disease, and (b) that educators of healthcare professional students can improve the educative experience by purposefully considering how a student's ontological self affects that student's practice.